Pengembangan Media Pembelajaran Fisika 3D Application Scratch Topik Pengukuran untuk Meningkatkan Hasil Belajar Peserta Didik - Wahyuni, Putri Dwi; Perdana, Riki (QUANTUM: Jurnal Pembelajaran IPA dan Aplikasinya, 2024)
AbstractPhysics is a complex and abstract subject. Students frequently struggle with comprehending physics material due to its abstract nature and the challenge of visualizing its concepts. Consequently, employing suitable educational tools becomes essential to facilitate students' comprehension of physics content. The utilization of learning aids stands as a pivotal element in enhancing the overall quality of physics education. Creating physics learning materials requires careful attention to various elements to ensure their effectiveness in aiding students' comprehension of physics concepts. The creation of the Scratch educational tools designed for measurement material aims to enhance students' motivation to learn, make learning more interesting and fun, and increase students' understanding of the measurement material. The aspiration is for the creation of Scratch-based educational resources tailored for high school class 10 measurement topics to serve as a viable option in enhancing the quality of learning materials for measurement. This study follows a developmental approach employing a 4D model encompassing (1) Defining, (2) Designing, (3) Developing, and (4) Disseminating. The analysis of the questionnaire test data indicates that the implementation of 3D Scratch-based physics learning applications focusing on measurement topics significantly enhances student learning outcomes, making it highly suitable for educational use. This is proven by the validation results of 3 aspects with a total display value of 3.58, access of 3.38, and language of 3.6.Keywords: Learning media, physics, measurement.AbstrakFisika merupakan mata pelajaran yang kompleks dan abstrak. Materi fisika sering kali tidak mudah bagi siswa untuk memahami karena melibatkan konsep yang rumit untuk dipahami. Karena itu, diperlukan alat bantu pembelajaran yang sesuai untuk mempermudah siswa untuk memahami materi pelajaran fisika.. Pemanfaatan alat bantu pembelajaran menjadi elemen krusial dalam meningkatkan standar pembelajaran fisika. Pengembangan media pembelajaran fisika perlu dilakukan dengan memperhatikan beberapa aspek supaya alat bantu pembelajaran yang dibuat mampu memberikan hasil efektif dalam menolong siswa memahami konsep fisika. Tujuan pengembangan media pembelajaran Scratch untuk materi pengukuran adalah menggalang semangat belajar siswa, menghadirkan pengalaman belajar yang lebih menarik dan seru, serta meningkatkan pemahaman siswa terhadap topik pengukuran. Pengembangan media pembelajaran Scratch untuk materi pengukuran di kelas 10 SMA diharapkan menjadi opsi yang dapat meningkatkan mutu pembelajaran dalam topik pengukuran. Studi ini adalah penelitian pengembangan yang menerapkan model 4D yang meliputi (1) Pendefinisian, (2) Perancangan, (3) Pengembangan, dan (4) Penyebaran. Dari data evaluasi berupa uji angket, disimpulkan bahwa penggunaan aplikasi fisika 3D Scratch pada topik pengukuran secara signifikan meningkatkan pencapaian belajar siswa, sehingga merupakan opsi yang sesuai untuk digunakan dalam pembelajaran. Hal ini terbukti Â dengan hasil validasi 3 aspek dengan nilai total tampilan sebesar 3.58, akses sebesar 3.38, dan bahasa sebesar 3.6.Kata-kata kunci: Media pembelajaran, fisika, pengukuran.